Effect of Different Type of Terpenes on Disulfiram Loaded Transdermal Invasomes Preparation and in-vitro Characterization - Worood Hameed AL-Zheery ,; Hanan Jalal Kassab, (Iraqi Journal of Pharmaceutical Sciences, 2025)
Disulfiram (DSF) is a thiocarbamate derivative that has been used for the treatment of alcoholism. Researchers recently found out that DSF, a medicine authorized by the FDA to prevent alcohol consumption, has been investigated for its potential in cancer treatment. DSF, when taken by mouth, undergoes extensive metabolism in the liver, making it unsuitable for cancer treatment via oral administration. Furthermore, DSF has demonstrated the ability to enhance the cytotoxic impact of anticancer medications while preserving healthy cells. To solve the problem of instability and insufficient therapeutic efficacy, invasomal vesicles developed with better entrapment efficiency and size to serve as a carrier for the transdermal delivery of disulfiram, The lipid vesicular carrier is used to evaluate the effects of different formulation variables, such as type and concentration of terpenes, on vesicle size, polydispersity index (PDI), and entrapment efficiency (EE). Nine invasome formulations were developed using the thin film hydration process. The optimized formula was further analyzed for its zeta potential, morphology, and in vitro release research to improve the DSF-IV8 formula. The DSF-IV8 invasome, which is composed of DSF, soya phosphatidylcholine (2%), carvacrol (1% w/v), and ethanol (40% v/v), demonstrated optimal characteristics, including spherical vesicles having a particle size of 119.2±2.2 nm, a PDI of 0.18±0.05, and an EE of 95.3±0.8%. The zeta potential value was measured to be -33.6±1.6 mV. The release pattern of DSF-IV8 showed an initial rapid release followed by a continuous release over 24 hours, in contrast to pure DSF which only had a release rate of 16%. Eventually, the thin film hydration approach was shown to be effective in formulating invasomal dispersion.